EChickAtlas: An introduction to the database. Issue 5 (30th March 2013) - Wong, Frances; Welten, Monique C.M.; Anderson, Claire; Bain, Andrew A.; Liu, Jiahui; Wicks, Michael N.; Pavlovska, Gordana; Davey, Megan G.; Murphy, Paula; Davidson, Duncan; Tickle, Cheryll A.; Stern, Claudio D.; et al.
<x xml:space="preserve">Abstract</x> The precise control of gene expression is critical in embryonic development. Quantitative assays, such as microarrays and RNA sequencing, provide gene expression levels for a large number of genes, but do not contain spatial information. In contrast, in situ methods, such as in situ hybridization and immunohistochemistry, provide spatial resolution, but poor quantification and can only reveal the expression of one, or very few genes at a time. Furthermore, the usual methods of documenting the results, by photographing whole mounts or sections, makes it very difficult to assess the three‐dimensional (3D) relationships between expressing and nonexpressing cells. Optical projection tomography (OPT) can capture the full 3D expression pattern in a whole embryo at a reasonable level of resolution and at moderately high throughput. A large database containing spatio‐temporal patterns of expression for the mouse (e‐Mouse Atlas Project, EMAP, www.emouseatlas.org) has been created, incorporating 3D information. Like the mouse, the chick is an important model in developmental biology and translational studies. To facilitate comparisons between these important model organisms, we have created a 3D anatomical atlas, accompanied by an anatomical ontology of the chick embryo and a database of gene expression patterns during chick development. This database is publicly available (www.echickatlas.org). genesis 51:365–371. © 2013 Wiley Periodicals, Inc.